Pemanfaatan Teknologi QR Code Dalam Menunjang Kegiatan Pada RPTRA Mardani Asri - Arifin, Yoseph Tajul; Irnawati, Oky; Watmah, Sri; Malau, Yesni (Jurnal Abdimas Komunikasi dan Bahasa, 2023)
Attendance is an activity that determines a person's level of discipline in an organization, school or company. Attendance levels can influence the productivity and sustainability of an organization's processes. Unclear attendance procedures or inconsistent attendance can result in errors in recording the attendance of participants in RPTRA activities, as well as reducing the motivation of administrators and participants in RPTRA activities. Mardani Asri Child-Friendly Integrated Public Space (RPTRA) is a public space concept in the form of an open space with human resources who are active as administrators at the Mardani Asri RPTRA consisting of PKK mothers, youth youth groups and local residents who have other jobs such as kindergarten teachers. It has activities including 10 PKK Programs and Sapa Posts, Disaster Services, Reading Gardens, Sports Places, Playgrounds. Problems related to absenteeism at RPTRAs (Child-Friendly Integrated Public Spaces) can be an important thing to pay attention to in RPTRA management because they can affect the effectiveness of programs and facility management. Utilizing QR Code technology for presence in RPTRA business management can help optimize operations and increase the effectiveness of existing work programs at the RPTRA. So training is needed on the use of QR Code technology to support the activities of the Mardani Asri RPTRA. The outputs to be achieved include articles in electronic media released on website media, as well as increasing knowledge and utilization of QR Code technology which can be implemented for activities at the Mardani Asri RPTRA. As for the results of this Community Service activity, RPTRA Mardani Asri participants were able to gain insight into QR Code technology and implement it for organizational needs. Kehadiran merupakan aktivitas yang menentukan tingkat kedisiplinan seseorang dalam suatu organisasi, sekolah maupun perusahaan. Tingkat kehadiran dapat berpengaruh pada produktifitas dan keberlangsungan proses suatu organisasi. Ketidakjelasan prosedur absensi atau absensi tidak konsisten dapat mengakibatkan kesalahan dalam mencatat kehadiran peserta dalam kegiatan-kegiatan di RPTRA, serta menurunkan motivasi pengurus maupun peserta kegiatan di RPTRA. Ruang Publik Terpadu Ramah Anak (RPTRA) Mardani Asri adalah konsep ruang publik berupa ruang terbuka dengan SDM yang aktif menjadi pengurus di RPTRA Mardani Asri terdiri dari Ibu-Ibu PKK, pemuda karang taruna serta warga sekitar yang memiliki pekerjaan lain seperti Guru TK. Memiliki kegiatan diantaranya 10 Program PKK dan Pos Sapa, Layanan Kebencanaan, Taman Bacaan, Tempat Berolahraga, Playground. Permasalahan terkait absensi di RPTRA (Ruang Publik Terpadu Ramah Anak) dapat menjadi hal yang penting untuk diperhatikan dalam manajemen RPTRA karena dapat mempengaruhi efektivitas program dan pengelolaan fasilitas. Pemanfaatan teknologi QR Code untuk presensi dalam manajemen usaha RPTRA dapat membantu mengoptimalkan operasional dan meningkatkan efektivitas program kerja yang ada di RPTRA tersebut. Maka dibutuhkan pelatihan pemanfaatan teknologi QR Code dalam menunjang kegiatan RPTRA Mardani Asri. Adapun luaran yang ingin dicapai antara lain artikel di media elektronik yang direlease dalam media website, serta peningkatan pengetahuan dan pemanfaatan teknologi  QR Code yang dapat diimplementasikan untuk kegiatan-kegiatan yang ada di RPTRA Mardani Asri.  Adapun hasil  dari kegiatan Pengabdian Masyarakat ini peserta RPTRA Mardani Asri dapat menambah wawasan mengenai teknologi QR Code dan mengimplementasikannya untuk kebutuhan organisasi.